2015
DOI: 10.1093/ntr/ntv213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Determinants for Cigarette Smoking Dependence in Mexican Mestizo Families

Abstract: The understanding of genetic and environmental determinants in the Mexican population is important for other Latin American populations as well, living in their own countries or moving to other ones, particular due to the current migration characteristics and particular genetic background like the Mexican Mestizo and other Central American populations with similar characteristics and migrating to neighbor developed countries, introducing their own smoking behavior and contributing importantly to the genetic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Regarding the CYP2A6 variants, Bloom et al reported that the rs1137115 and rs28399435 were associated with low metabolism of nicotine in European Americans [33], but in our study no differences were observed among urinary levels of nicotine, cotinine and 3HC with these variants. The variant rs28399433 has been reported to be associated with smoking dependence in Mexican population [34], but no association was observed in our study at large. Nevertheless, when stratifying our samples according to their NMR, only the single sample that fell into the slow metabolizer category (NMR < 0.31) presented with a heterozygous genotype for the rs28399433 variant.…”
Section: Discussioncontrasting
confidence: 96%
“…Regarding the CYP2A6 variants, Bloom et al reported that the rs1137115 and rs28399435 were associated with low metabolism of nicotine in European Americans [33], but in our study no differences were observed among urinary levels of nicotine, cotinine and 3HC with these variants. The variant rs28399433 has been reported to be associated with smoking dependence in Mexican population [34], but no association was observed in our study at large. Nevertheless, when stratifying our samples according to their NMR, only the single sample that fell into the slow metabolizer category (NMR < 0.31) presented with a heterozygous genotype for the rs28399433 variant.…”
Section: Discussioncontrasting
confidence: 96%
“…We found differences among two cessation programs in two SNPs, rs28399433 and rs2431413; previously, the rs28399433 showed reduced apparent oral efavirenz clearance [ 23 ]; regarding nicotine metabolism, women and normal nicotine metabolizers (harboring the common allele) may benefit more from varenicline over nicotine replacement therapy [ 24 ]. Previously, our workgroup identified an association with a younger age at onset smoking [ 16 ], smoking status, age of onset, and psychological dependence in Mexican mestizo families [ 15 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to single nucleotide variants analyzed in the genes related to those involved in the dopaminergic and serotonergic pathways, we identified differences in the genotype frequency among both groups in three SNPs in NRXN1 gene, the rs10189159, rs985919, and rs1882296; the latter revealed in an in silico analysis that rs1882296/T had a high level of homology with Hsa-miR-6740-5p, which encodes a putative miRNA that targets glutamate receptor subunits (GRIA2, GRID2) and GABA receptor subunits (GABRG1, GABRA4, GABRB2). In contrast, rs1882296/C had a high homology level with Hsa-miR-6866-5p, which encodes a different miRNA that targets GRID2 and GABRB2 [ 25 ], proposing new hypotheses regarding the putative roles of miRNAs that influence the GABAergic and glutamatergic pathways in smoking addiction. Otherwise, two SNPs in CHRNA3 had statistically significant differences in genotype frequencies, rs1317286 and rs615470.…”
Section: Discussionmentioning
confidence: 99%
“…A different pattern occurs in African populations; African and African American show a frequency of 7-10 % (Ho et al, 2009[49]; Mwenifumbo et al, 2008[87]; Nakajima et al, 2006[91], 2004[95]; Schoedel et al, 2004[117]), but in populations with a more conserved African component as Ghanaian (5.7 % (Gyamfi et al, 2005[45])) and Ethiopian (2.8 % (Aklillu et al, 2014[1])) the frequency is lower. Amerindian populations such as Canadian natives (15.5 % (Schoedel et al, 2004[117])) and Alaskan Yupik (8.9 % (Binnington et al, 2012[16])) had a heterogeneous frequency, which was the same as American mestizo populations such as Brazilian (5.7 % (Vasconcelos et al, 2005[139])), Ecuadorian (10.3 % (Soriano et al, 2011[124])), Mexican (16.4 % (Svyryd et al, 2015[126])) and other Hispanics (7.1 % (Benowitz et al, 2006[13])). The only population in Oceania to report this allele is the native population Māori from New Zealand with 19 % (Lea et al, 2008[71]).…”
Section: Population Distribution Of Cyp2a6 Allelesmentioning
confidence: 97%